The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-313x.2007.03056.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural analogs of ABA reveal novel features of ABA perception and signaling in Arabidopsis

Abstract: SummaryChanges in gene expression produced by the application of (+)-abscisic acid (ABA) to Arabidopsis thaliana plants were compared with changes produced by the ABA structural analogs ())-ABA, (+)-8¢-acetylene ABA and ())-2¢,3¢-dihydroacetylenic abscisyl alcohol. The maximum expression of many rapidly (+)-ABA-induced genes occurred prior to peak hormone accumulation, suggesting negative feedback regulation that may be mediated by the induction of genes encoding PP2C-type protein phosphatases. For most rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(132 citation statements)
references
References 68 publications
(164 reference statements)
6
125
0
1
Order By: Relevance
“…These results of mDr and pDr are consistent and reveal the similarity in significance of ABA-and non-ABA-related or -dependent pathways in drought responses. In genome-wide oligonucleotide microarray studies of Arabidopsis soil water deficit pDr responses (Huang et al, 2008), a higher level of drought-regulated genes was found in comparison with ABA responses using a more response-eliciting ABA analog (Huang et al, 2007).…”
Section: Drought Transcriptome Analysismentioning
confidence: 99%
“…These results of mDr and pDr are consistent and reveal the similarity in significance of ABA-and non-ABA-related or -dependent pathways in drought responses. In genome-wide oligonucleotide microarray studies of Arabidopsis soil water deficit pDr responses (Huang et al, 2008), a higher level of drought-regulated genes was found in comparison with ABA responses using a more response-eliciting ABA analog (Huang et al, 2007).…”
Section: Drought Transcriptome Analysismentioning
confidence: 99%
“…Primer specificity was checked with BLASTn searches against TAIR10 transcripts (http://www.arabidopsis.org/) as well as by monitoring melt curve using the ABI StepOne Real-time PCR systems (Applied Biosystems). ACTIN2 (At3g18780) was used as an endogenous control for standardization (Huang et al, 2007). Real-time qRT-PCR was performed with Power SYBR Green PCR Master Mix (Applied Biosystems), and amplification was monitored with StepOne real-time PCR systems.…”
Section: Real-time Qrt-pcr Analysesmentioning
confidence: 99%
“…A similar GA-hypersensitive phenotype was also observed in RAB18:ENY seedlings when grown under 10 mM GA 3 and 0.45 mM (+)-ABA to induce ENY, but only with respect to increased hypocotyl elongation (see Supplemental Figure 12 online). A mild phenotype was not unexpected, however, as ENY expression would not be sustained under the RAB18 promoter, partly because ABA was applied at a low concentration and would be rapidly metabolized (Huang et al, 2007).…”
Section: Eny Is a Negative Regulator Of Photomorphogenesis In The Prementioning
confidence: 99%